Determinants of community participation in a watershed development program in Southern Ethiopia. Issue 2 (15th March 2022) - Roba Gamo, Bereket; Woldeamanuel Habebo, Teshale; Tsegaye Mekonnen, Genene; Park, Duk-Byeong
ABSTRACT: Community participation is critically important for the effectiveness of a development project. Different factors influence community participation, and these factors are not the same across all communities. This study aimed to identify the socioeconomic and watershed impact-related factors influencing community participation in a watershed development program in southern Ethiopia. Data were collected from 1, 064 respondents (87.7% males) and in nine districts in southern Ethiopia. Descriptive statistics and logistic regression explored which variables predict higher rates of community participation, and whether determining variables changed from before to after the program was implemented. The results show that the variables predicting community participation in the watershed development program were significantly different before and after the program's implementation. The findings highlight the importance of demonstrating the positive impacts of community development interventions as early in the program as possible to ensure more and continued participation in relevant development projects.